Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T22:53:19+01:00
A) 5(x-2)+2x = 5x-10+2x=7x-10
b)-4(2y+1)+y= -8y-4
c)5y-3(y-1)= 5y-3y+3=2y+3
d)(12x-4):4+1+x= 3x-1+1+x=4x
e)-3(x-7)-(x+2)=-3x+21-x-2= -4x+19
f)-(x+2)-3(2x-4)+2(x-1)=-x-2-6x+12+2x-2= -5x+8
2010-03-18T23:40:11+01:00
A. 5(x-2)+2x=5x - 10 + 2x = 7x - 10
b. -4(2y+1)+y=-8y + (-4) + y = -7y -4
c. 5y-3(y-1)=5y - 3y +3 = 2y +3
d. (12x-4):4+1+x= 3x - 1 + 1 + x = 4x
e. -3(x-7)-(x+2)= -3x + 21 - x - 2 = -4x + 19
f. -(x+2)-3(2x-4)+2(x-1)= -x -2 -6x + 12 + 2x -2 = -5x + 8